Prosedur dan Efektifitas Mekanisme Penyelesaian Sengketa Perdagangan dan Investasi Dalam Asean - Anggia Rettrisunz P I M Panjaitan (Universitas Ekasakti, 2024)
The Association of South-East Asian Nations Enhanced Dispute Settlement Mechanism (ASEAN EDSM), like the World Trade Organization's (WTO) Dispute Settlement Mechanism, recognizes trade countermeasures in the event of noncompliance with Panel and Appellate Body rulings. However, the harmed party may encounter stumbling obstacles while proposing an authorized trade countermeasure. The pitfall emphasizes the implications of not resolving the conflict. Meanwhile, ASEAN acknowledges a system that allows disputant states to present outstanding disputes to the ASEAN Summit under Article 26 of the ASEAN Charter. Furthermore, if the injured party is harmed as a result of the ASEAN dispute settlement decision's failure to be implemented, the injured party may raise the issue at the ASEAN Summit in accordance with Article 27(2) of the ASEAN Charter. This study looks into whether the involvement of the ASEAN Summit may help solve the post-adjudication problem in the ASEAN EDSM. The research methods include a literature review and a thorough reading of Articles 26 and 27 of the ASEAN Charter